Pengaruh Religiusitas dan Pemahaman Qanun Terhadap Minat Menabung Nasabah Pada PT BRISyariah Lhokseumawe Pasca Konversi - Juliana lia Putri (ITB AAS INDONESIA Surakarta, 2022)
Abstract This study aims to determine and analyze the influence of religiosity (X1) and understanding of Qanun (X2) on customers' interest in saving at PT BRISyariah Lhokseumawe Post-Convention. In this study using quantitative research methods. The population in this study were all customers of Bank BRISyariah Kota Lhokseumawe, and the number of samples used in this study were 100 customers. Sampling in this study is using purposive sampling technique, which is a technique of determining the sample based on chance, by distributing questionnaires to customers who are deemed suitable to be used as research data. The data collection method was done by using a questionnaire. The analysis technique used is the Validity Test, Reliability Test, T Test, F Test, R Test, and Multiple Linear Regression Test. In this study using the SPSS IBM 22 data analysis test toolBased on the T test, it shows that the Religiosity variable (X1) has a significant effect on the interest in becoming a customer (Y). Understanding Qanun (X2) has a positive and significant effect on the interest in becoming a customer (Y). Based on the F test, it shows that the dependent variables (religiosity, understanding of qanuns) together significantly influence the independent variable (interest in becoming a customer).